A broadly tunable multiple wavelength Brillouin-erbium fiber laser utilizing stimulated Brillouin scattering as a virtual mirror. - Mahdi, Mohd Adzir; Ajiya, Mohammed; Al-Mansoori, Mohammed Hayder (2013)

(untitled)
The present invention relates to a broadly tunable wavelengths Brillouin/erbium fiber laser. The said broadly tunable multiple wavelengths Brillouin/erbium fiber laser can be tuned over Brillouin pump wavelengths. The present invention comprises of a Brillouin pump source (10), a pair of optical directional couplers (12) and (20). Further to this the present invention also comprises of an erbium doped fiber (18) and a wavelength selective coupler (hereinafter also referred as WSC) (14). The present invention also comprises of a 3-port optical circulator (28), a dispersion compensating fiber (DCF) (24), an optical isolator (26), an output (22) through which the systems output channels can be extracted.